The impact of interdisciplinary case management on client outcomes. - Slack MK; McEwen MM (Family & Community Health)
To assess impact, outcome data were analyzed from an interdisciplinary case management program based on the Omaha Systems model. The study population of 54 clients was 98 percent female and 98 percent Hispanic, with 65 percent having not completed high school. Clients averaged seven problems: 43 percent were psychosocial, 23 percent environmental. 19 percent physiological, and 15 percent healthrelated behaviors. Interventions (12.4/client) were primarily educational (53%) and case management (19%). Effect sizes for impact were moderate to very large (0.4 to 1.5: p < 0.002) for knowledge, behavior, and status outcomes. The results indicate that interdisciplinary case management using the Omaha Systems model can affect significantly outcomes related to specific problems. Copyright (c) 1999 by Aspen Publishers, Inc.